Solve by Monge’s method
Comparing the given equation with "Rr+Ss+Tt=V,"we have "R=1, S=a+b,T=ab,V=xy."
Here Monge’s subsidiary equations
"Rdy^2-Sdxdy+Tdx^2=0"
become
"dy^2-(a+b)dxdy+abdx^2=0 \\ \\ \\ \\ \\ \\ \\ \\ (2)"
Equation "(2)" may be factorised as
"(dy-adx)=0 \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ (4)"
On integration
"y-ax=c_2 \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ (6)"
Combining equation (3) with subsidiary equation (1), we get
"dp+adq-xydx=0"
By using (5)
On integration, we get
By using (5)
"p+aq-(\\dfrac{1}{2})x^2y+(\\dfrac{1}{6})bx^3=c_3"
Therefore the first intermediate integral is
Similarly, the second intermediate integral corresponding to equation (4) is
Now from above two intermediate integrals (7) and (8), we deduce the values of p and q as
"p=\\dfrac{1}{2}x^2y-\\dfrac{1}{6}(a+b)x^3+\\dfrac{1}{a-b}\\big[af_2(y-ax)-bf_1(y-bx)\\big]"
Substituting these values of "p" and "q" in "dz=pdx+qdy," we get
"+\\dfrac{1}{a-b}\\big[af_2(y-ax)dx-bf_1(y-bx)dx\\big]+"
"+\\dfrac{1}{6}x^3dy+\\dfrac{1}{a-b}\\big[f_1(y-bx)dy-f_2(y-ax)dy\\big]"
Or
"-\\dfrac{1}{b-a}\\big[af_2(y-ax)dx-bf_1(y-bx)dx\\big]-"
"-\\dfrac{1}{b-a}\\big[f_1(y-bx)dy-f_2(y-ax)dy\\big]"
Or
"+\\dfrac{1}{b-a}f_2(y-ax)(dy-adx)-"
"-\\dfrac{1}{b-a}f_1(y-bx)(dy-bdx)"
Integrating, we get the required solution as
Comments
Leave a comment